A Game Optimization Scheduling Strategy of Active Distribution Network With Multi-Microgrid Sharing Energy Storage - Li, Fei; Li, Xianshan; Fang, Zijian; Zhang, Lei (Frontiers in Energy Research, 2022)
In a multi-microgrid grid-connected system, a MGCO is formed to participate in the optimization scheduling of the ADN by sharing ES, which can promote the efficient utilization of resources and obtain win–win interests for all participants. According to the complementary characteristics of ES behaviors and energy production–consumption of MGs, a game scheduling model of the ADN with the MGCO for sharing ES is established to obtain energy reciprocity and balance the interest of both parties. The ADN formulates the ToU price policy to maximize the operational benefits, and the MGCO responds to the price to obtain each member’s energy-dispatching strategy for minimizing the total operating costs. Furthermore, all members in the MGCO distribute the cooperation surplus based on the Shapley value method. The example results show that the proposed game model can balance the benefits between the ADN and multi-microgrid with sharing ES and maximize the mutual benefits of the MGCO through energy reciprocity.